Penegakan Hukum terhadap Pelaku Pelecehan Seksual Modus Child Grooming di Polres Tebing Tinggi: Perspektif Hukum Pidana Islam - Ramadhani, Anggi; Ramadani, Ramadani (Fakultas Hukum, Universitas Muslim Indonesia, 2024)
This study aims to identify cases of child grooming sexual abuse in Tebing Tinggi City, identify the types of sanctions that can be imposed on groomers from the perspective of Islamic criminal law, and examine the law enforcement efforts undertaken by the Tebing Tinggi Police Resort in handling these cases. This research employs a mixed-methods approach, combining field research and normative legal analysis. The collected data is then analyzed qualitatively to describe the issue and address the research objectives. The results show that child grooming cases at the Tebing Tinggi Police Resort fluctuated throughout 2019-2024, with a significant surge of 70 cases in 2023. The standard modus operandi involves establishing an emotional relationship and trust between the groomer and the victim, which the groomer then exploits to commit sexual abuse. From the perspective of Islamic criminal law, groomers can be subjected to hadd punishment if sexual intercourse occurs or ta’zir punishment if only sexual abuse without intercourse takes place. Simultaneously, the Tebing Tinggi Police Resort has carried out its law enforcement function both repressively, through the process of investigation, inquiry, and determination of suspects based on the provisions of Law Number 8 of 1981 and Law Number 23 of 2002, and preventively, through education and outreach programs. Therefore, it is recommended that the Tebing Tinggi Police Resort, the Tebing Tinggi City Government, community institutions, religious leaders, families, and parents enhance their efforts in preventing and handling child grooming comprehensively and continuously.